2004
DOI: 10.1002/mrm.20008
|View full text |Cite
|
Sign up to set email alerts
|

MR properties of excised neural tissue following experimentally induced inflammation

Abstract: Changes in the MR parameters of inflamed neural tissue were measured in vitro. Tumor necrosis factor-alpha (TNF-␣) was injected into rat sciatic nerves to induce inflammation with negligible axonal loss and demyelination. The MR parameters, such as T 1 /T 2 relaxation and magnetization transfer (MT), were measured 2 days after TNF-␣ injection and were found to be substantially different from those of normal nerves. The average T 1 /T 2 relaxation times increased, whereas the MT ratio (MTR) and the quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
140
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 26 publications
3
140
0
Order By: Relevance
“…Although the sensitivity of T 2 to detect changes in myelin has been an issue of debate, myelin content had been reported to correlate with T 2 (MacKay et al, 1994;Stanisz et al, 2004). We have no definitive explanation for this apparent discrepancy.…”
Section: Dti Of Wt Shi and Transplanted Mice At Short T Diffmentioning
confidence: 69%
“…Although the sensitivity of T 2 to detect changes in myelin has been an issue of debate, myelin content had been reported to correlate with T 2 (MacKay et al, 1994;Stanisz et al, 2004). We have no definitive explanation for this apparent discrepancy.…”
Section: Dti Of Wt Shi and Transplanted Mice At Short T Diffmentioning
confidence: 69%
“…Real T 2 increases likely to be present in the case of true edema clearly affected the observed ͗T 2 ͘ and ͗T 2ie ͘; moreover, we observed that the position of the ͗T 2ie ͘ peak in the distribution does not strictly follow the model value of T 2ie but is underestimated by the QT2 analysis. The different effects of demyelination and edema on the T 2 distribution may allow the distinction of the two effects using in vivo imaging in human WM, as previously suggested by Stanisz and colleagues (33,39). A linear relationship was assumed between increases in the IE water content and T 2ie in these simulations as the functional form of this relationship is not distinguishable from published data (33): better knowledge regarding this relationship would help determine the potential of QT2 to distinguish between edema and demyelination.…”
Section: Clinical Implications: Pathology Modelsmentioning
confidence: 85%
“…Specifically, we performed simulations reducing both compartments by the same relative amount of 25 to 100%. Finally, edema simulations were also performed with increases of up to 25% in the IE water compartment size, in 5% steps, increases larger than reported in MS (32) but selected to cover of the potential range of experimentally induced inflammation (33). In addition, these simulations were performed with and without an increase of T 2ie of up to 100%, linearly scaled with the increase of IE water content.…”
Section: Modification Of the Modelmentioning
confidence: 99%
“…For specifically identifying axon injury and loss, reduced NAA content measured by magnetic resonance spectroscopy (MRS) has been used (De Stefano et al, 1999;Aboul-Enein et al, 2010;Wood et al, 2012). However, inflammation can interfere with measuring myelin and axons because inflammation-induced tissue swelling falsely reduces the measured myelin water and NAA content (oedema water contains no NAA and dilutes myelin water fraction), MTR (oedema water exhibits no transfer effect while contributing to the total signal), and PET marker intensity (diluting marker density) (Schmierer et al, 2004;Stanisz et al, 2004;McCreary et al, 2009;Vavasour et al, 2011). Despite that DTI-derived axial diffusivity and radial diffusivity can concurrently quantify coexisting axonal injury and demyelination in some settings (Song et al, 2002(Song et al, , 2003(Song et al, , 2005, DTI becomes inaccurate in the presence of inflammation (Sun et al, 2006b;Lodygensky et al, 2010;Xie et al, 2010), tissue loss (Kim et al, 2007), crossing fibres (Wheeler-Kingshott and Cercignani, 2009), and CSF contamination (Karampinos et al, 2008;Cheng et al, 2011) and cannot measure the inflammatory components.…”
Section: Discussionmentioning
confidence: 99%